First report of non-marine ostracods (Crustacea, Ostracoda) from the Dahlak Archipelago (Eritrea), with the description of two new species - Giampaolo Rossetti; Ilaria Mazzini; Giorgio Chiozzi; Luca Vecchioni; Federico Marrone (Journal of Limnology)
The information on Recent non-marine ostracod faunas of the north-eastern part of the Afrotropical region is still limited. Here we report the first record of ostracods from the Dahlak Archipelago, a group of small islands located in the southern part of the Red Sea off the Eritrean coast. Specimens were obtained by hatching in the laboratory of diapausing eggs occurring in dried mud collected in temporary freshwater ponds, following the so-called “Sars’ method”. A total of five species were found, including two species new to science, of which four belong to the family Cyprididae (Cypris galefensis, Plesiocypridopsis newtoni, Heterocypris sp., and Chrissia martensi n.sp.) and one to the family Ilyocyprididae (Ilyocypris dahlakensis n.sp.). A detailed description of the morphology of valves and soft parts is given, and COX1 sequences were obtained for four species. Cypris galefensis was so far only known for its type locality in Somalia with a population containing both males and females, whereas our samples consisted exclusively of females. Plesiocypridopsis newtoni, a species characterised by a wide geographic distribution and previously known to occur also in the Afrotropical region, shows marked variability in the prehensile palps of males, as evidenced by comparing the specimens from this study with descriptions available in the literature. The genus Heterocypris (with 15 species) and the genera of the two new species described here, Chrissia (with 17 species) and Ilyocypris (with four species), have been previously reported from this biogeographic region as well. The specimens analysed of Chrissia martensi n.sp. were all females, none of which had sperm inside the carapace, indicating the possibility of parthenogenetic reproduction in this species. A peculiar sexual dimorphism in the valve morphology characterises Ilyocypris dahlakensis n.sp., with females having a straight posterior margin, forming a right angle at the ventral anterior edge. Rehydration of dry sediments collected from arid areas where wet periods are short and often unpredictable has proven to be a successful method for describing aquatic invertebrate biodiversity.